Palladium-Catalyzed Oxidative Heck Coupling of Vinyl Pyridines with Aryl Boronic Acids - Chen, Shanshan; Zhang, Xiuli; Chu, Mingjie; Gan, Xiaoping; Lv, Xianhai; Yu, Jie (Synlett, 2015)
An efficient methodology has been developed for the oxidative cross-coupling of vinyl pyridine with various boronic acids catalyzed by palladium. In this reaction, vinyl pyridines reacted with various aryl boronic acids in the presence of 10 mol% palladium(II) trifluoroacetate, 10 mol% 1,10- phenanthroline, and 1 equivalent silver(I) oxide, to give the corresponding aryl vinyl pyridine products as a single stereoisomer, with N,N-dimethylformamide as the solvent and under 1 atmosphere of oxygen gas. The aryl vinyl pyridine products were obtained in moderate to good yields after 24 hours. A mechanism for the reaction is proposed.
Keywords: oxidative Heck coupling; palladium catalyst; vinyl pyridine; boronic acid